2014
DOI: 10.1155/2014/724804
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Social Support on Symptoms of Anxiety and Depression among Patients with Silicosis

Abstract: The improvement of social support promotes the mental health and improves the health status. The study aimed to examine the influence of the social support on symptoms of anxiety and depression among patients with silicosis and provide the scientific basis to further alleviate anxiety and depression and to monitor their whole quality of life. We investigated 324 inpatients with silicosis between April 2011 and September 2011. The HADS (the Hospital Anxiety-Depression Scale) was the major methodology used to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
0
20
0
4
Order By: Relevance
“…However, this association has not been discussed in Chinese rural institutional elders. Additionally, the predictive function of perceived social support for other mental illness, such as anxiety and depression, has also been confirmed by recent evidence in populations of different age groups (Han et al 2014;Olagunju et al 2015). Moreover, the function of social support might be particularly important for the Chinese population, whose value system emphasizes a collectivistic culture and interpersonal harmony (Zhang et al 2005).…”
Section: Modelsmentioning
confidence: 81%
See 1 more Smart Citation
“…However, this association has not been discussed in Chinese rural institutional elders. Additionally, the predictive function of perceived social support for other mental illness, such as anxiety and depression, has also been confirmed by recent evidence in populations of different age groups (Han et al 2014;Olagunju et al 2015). Moreover, the function of social support might be particularly important for the Chinese population, whose value system emphasizes a collectivistic culture and interpersonal harmony (Zhang et al 2005).…”
Section: Modelsmentioning
confidence: 81%
“…Additionally, the predictive function of perceived social support for other mental illness, such as anxiety and depression, has also been confirmed by recent evidence in populations of different age groups (Han et al . ; Olagunju et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Although our study is the first of its kind in CIF, potential wider implications of our findings can be drawn on from similar studies in other chronic conditions. For example, in patients with chronic generalized pain, higher levels of perceived social support have been associated with lower levels of depression, and levels of perceived social support as measured by MSPSS were found to significantly influence anxiety and depression symptoms in inpatients with silicosis . Moreover, epidemiological studies have indicated that individuals with low levels of social support have higher mortality rates, especially from cardiovascular disease .…”
Section: Discussionmentioning
confidence: 99%
“…Hingegen fallen die klinisch relevanten Angstwerte mit 12,9 % geringer aus [39]. Schließlich weisen Untersuchungsergebnisse darauf hin, dass Frauen mit Silikose stärker von Depressionen betroffen sind als Männer [19]. Dieser geschlechtsspezifische Unterschied in Bezug auf depressive Symptome zeigt sich auch in der Studie zur Gesundheit Erwachsener in Deutschland (DEGS) des Robert Koch-Instituts [18].…”
Section: Prävalenz Von Depressiven Und äNgstlichen Symptomen Bei Pneuunclassified
“…Da die psychische Gesundheit von Patienten unter anderem in Verbindung mit der Compliance der Medikamenteneinnahme, der Wirkung von Therapien sowie dem Umgang mit der zunehmenden Erkrankungsschwere steht [17,19], sollte diese im Krankheitsmanagement nachhaltig verbessert werden. Dazu stehen verschiedene Therapiemöglichkeiten zur Verfügung.…”
Section: Infoboxunclassified